How green investment drives sustainable business performance for food manufacturing small‐ and medium‐sized enterprises? Evidence from an emerging economy. (9th February 2022) - Le, Thanh Tiep; Ferasso, Marcos
Abstract: This study unfolds the nexus between green investment (GI), the sustainable business performance (SBP) of small‐ and medium‐sized enterprises by exploring the mediating role of corporate social responsibility (CSR), and green innovation (GIN) in the context of an emerging economy. A well‐structured questionnaire was used for data collection. A total of 556 valid responses from directors and managers were received and used for data analysis. The Smart PLS version 3.3.2 was employed to analyse and investigate the relationships between the constructs and the latent variables. Our findings provide an insight into how GI can boost SBP in the context of CSR and GIN partially mediating this relationship. This research implies that, businesses, which implement GI, GIN and CSR to promote bringing long‐term and sustainable benefits to businesses and stakeholders for SBP to help businesses, develop sustainably in the new context.